2008
DOI: 10.1016/j.schres.2007.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of glutamate carboxypeptidase II in psychiatric disease

Abstract: Experimental evidence is beginning to converge on an important role for dysregulation of glutamate carboxypeptidase II (GCPII) in schizophrenia. The goal of this study was to determine GCPII levels in postmortem brain specimens of patients with schizophrenia, bipolar disorder or unipolar depression and age-matched control subjects. We used, a high-affinity radioligand for GCPII, to probe for GCPII expression in prefrontal cortex (PFC) and mesial temporal lobe, two brain regions implicated in the pathophysiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 45 publications
2
26
0
1
Order By: Relevance
“…Other studies have demonstrated changes in gene expression patterns in BA9 in psychiatric disorders (Digney et al, 2005;Veldic et al, 2005;Guilarte et al, 2008). Within BA9, we detected diminished VGF in layer VI.…”
Section: Vgf Mrna Is Reduced In Human Bipolar Postmortem Brainssupporting
confidence: 61%
See 1 more Smart Citation
“…Other studies have demonstrated changes in gene expression patterns in BA9 in psychiatric disorders (Digney et al, 2005;Veldic et al, 2005;Guilarte et al, 2008). Within BA9, we detected diminished VGF in layer VI.…”
Section: Vgf Mrna Is Reduced In Human Bipolar Postmortem Brainssupporting
confidence: 61%
“…CA2 is an important information processing point between the dentate gyrus and the subiculum (Heckers et al, 2002). CA2 has also been implicated in psychiatric disorders (Benes et al, 2001;Knable et al, 2004;Dean et al, 2005), and, in particular, studies suggest a dysfunction of CA2 inhibitory GABAergic interneurons in severe mental illness (Müller et al, 2001;Tian et al, 2007;Guilarte et al, 2008). Our findings of reduced VGF expression in CA2 pyramidal cells of bipolar disorder patients suggest that, in addition to the alterations in inhibitory interneurons, there may be changes in the function of excitatory neurons.…”
Section: Vgf Mrna Is Reduced In Human Bipolar Postmortem Brainsmentioning
confidence: 57%
“…Consistent with the hypothesis that GCPII regulates glutamate transmission, GCPII inhibitors have been shown to possess therapeutic utility in many preclinical models of neurodegenerative diseases with presumed underlying glutamate aberrations (Neale et al, 2005;Barinka et al, 2012). In addition, abnormal NAAG and GCPII levels have been detected in tissue samples from preclinical animal models and patients with neurodegenerative disorders, including amyotrophic lateral sclerosis (Tsai et al, 1991;Plaitakis and Constantakakis, 1993;Ghadge et al, 2003), epilepsy (Meyerhoff et al, 1992;Pacheco Otalora et al, 2007), schizophrenia (Ghose et al, 2004;Guilarte et al, 2008;Profaci et al, 2011), and Huntington's disease (Passani et al, 1997). Glutamate has also been widely implicated in pain perception, so consequently there has been interest in the development of potent orally available GCPII inhibitors as therapeutics for chronic pain states .…”
Section: Introductionmentioning
confidence: 99%
“…Protein expression and functionality of FOLH1 may therefore play an important role in the pathophysiology of psychiatric disorders. 151 It is possible that worse outcomes in patients with variant FOLH1 may be due to a GCPII functionality in the brain and its effect on the depressive symptoms rather than the FOLH1 effect on folate levels. So this is an encouraging observation that requires considerable further investigation.…”
mentioning
confidence: 99%